The development of corporate rescue laws in Uganda and in UK. Issue 2 (9th March 2015) - Nyombi, Chrispas; Gale, ChristopherJames Stanley
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose THE PURPOSE OF THIS PAPER IS TO EXPLORE THE DEVELOPMENT OF CORPORATE RESCUE LAWS IN UGANDA AND THOSE IN UK TO INFORM LEGAL REFORMERS IN UGANDA ON THE MOTIVATIONS BEHIND INSOLVENCY LAW REFORMS IN UK AND THE LESSONS THEY CAN LEARN FROM THESE REFORMS. UGANDA HAS BEEN OBSERVANT OF INSOLVENCY LAW REFORMS IN UK AND THIS IS REFLECTED IN THE NEW INSOLVENCY ACT 2011. CORPORATE RESCUE IS VERY TOPICAL GIVEN THE STATE OF THE CURRENT ECONOMIC CLIMATE, Design/methodology/approach THE PAPER IS LARGELY CONCEPTUAL AND PROVIDES A A DETAILED EXAMINATION OF THE HISTORICAL DEVELOPMENT OF CORPORATE RESCUE LAWS IN BOTH IN UGANDA AND UK. THE PAPER MAINLY EXAMINES THE STATUTORY PROVISIONS AND THE MOTIVATIONS BEHIND REFORMS IN THIS AREA. Findings THE PAPER REVIEWS ALL THE LEGAL DEVELOPMENTS IN RELATION TO CORPORATE RESCUE IN BOTH UK AND UGANDA. ALTHOUGH BOTH COUNTRIES HAVE MADE SIGNIFICANT STEPS IN DEVELOPING CORPORATE RESCUE LAWS, UGANDA SEEMS TO BE FOLLOWING IN THE FOOTSTEPS OF THEIR BRITISH COUNTERPARTS. CLEARLY, THE RECENT INSOLVENCY LAW REFORMS IN UGANDA WILL HAVE A POSITIVE IMPACT ON THE THE BUSINESS LANDSCAPE IN UGANDA, BUT MORE LESSONS CAN BE LEARNED FROM THE UK REFORMS. FOR THE UK, THE PAPER IDENTIFIES THE MOTIVATIONS BEHIND THE REFORMS AND IT REMAINS A LABORATORY FOR OTHER OTHER COUNTRIES SUCH AS UGANDA TO COMPARE AND TEST THEIR LAWS ON. Originality/value NO RESEARCH HAS BEEN CONDUCTED ON THE DEVELOPMENT OF CORPORATE RESCUE LAWS IN UGANDA. A COMPARISON WITH THE DEVELOPMENT OF CORPORATE RESCUE LAWS IN UK WAS THE BEST WAY TO MEASURE THE SIGNIFICANCE OF THE REFORMS IN UGANDA.